Research of the Modeling of Globoidal Indexing Cam with Tapered Roller and Motion Simulation based on Adams - Zhao Shitian; Fu Yingying; Yang Xiangguo; Wu Shuhang; Fang Luanjun (Jixie chuandong)
Construction method of the universal surface equation of the globoidal indexing cam mechanism with tapered roller is presented based on transformation of homogeneous coordinate after the theoretical analysis of conjugate surface theory and the differential geometry. Data collection system of the undeveloped ruled surface points is developed based on VB and the 3D modeling of the indexing mechanism is set up in Creo. Motion simulation and analysis of the mechanism is carried out in Adams. Simulation example is carried out by the proposed method. The result shows that the designed globoidal indexing cam mechanism with tapered roller satisfied the indexing expectation.